Análisis comparativo de los marcos normativos sobre cultivos nativos y semillas en Bolivia, Ecuador y Perú: avances y desafíos - Ruiz Muller, M. (2025)
The document provides a comparative analysis of the legal frameworks, public policies, and institutions governing native crops and seeds in Bolivia, Ecuador, and Peru. It explains how numerous regulatory instruments developed in recent decades often overlap, creating complexity in understanding their goals and implementation. The text highlights the increasing recognition of smallholder Andean farmers and the importance of native crops for food security and climate adaptation. It also shows how national progress aligns with international trends, emphasizing that the upcoming meeting of the ITPGRFA Governing Body offers a timely opportunity to assess advances and remaining challenges.